A decision modeling approach for smart e-tourism data management applications based on spherical fuzzy rough environment - Alamoodi, Abdullah Hussein (Tanjung Malim, 2023)
A decision modeling approach for smart e-tourism data management applications based on spherical fuzzy rough environment by Alamoodi, Abdullah Hussein